Pengaruh Stress Kerja dan Beban Kerja terhadap Turnover Intention dengan Moderasi Kepuasan Gaji - Intan Nia Ruhyat; Safira Jingga Hernita; Abdul Riduwan; Iwan Eko Ariyadi (Target : Jurnal Manajemen Bisnis, 2021)
The occurrence of turnover is something that is not desired by the company and often results in losses for the company both in terms of costs, time and resources used. The purpose of this study is to examine the effect of work stress, workload, on turnover intention which is moderated by salary satisfaction. This research was conducted by distributing 36 questionnaires to 40 respondents who were active employees of the company who received salaries. The test was carried out with the help of statistical tools in the form of Structural Equation Modeling (SEM) based on Partial Least Square version 3 by taking into account the factor loading value = 0.6, composite reliability with a value = 0.7 and the variance extracted value = 0.50. The results show that the independent variable workload has a significant positive effect on turnover intention. Likewise, the independent variable work stress also has a significant positive effect. As well as the moderating variable Salary Satisfaction weakens the relationship between workload and work stress. Keywords: workload, salary satisfaction, work stress, turnover intention